Turquoise killifish - Reichard, Martin; Cellerino, Alessandro; Valenzano, Dario R (Current biology, 2015)
Reichard et al. introduce the turquoise killifish (Nothobranchius furzeri), notable for its short-life span and diapause stage.
Keywords: Longevity; Aging; Animals; Afrika; modely u zvířat; Africa; Models, Animal; Cyprinodontiformes; zvířata; stárnutí; dlouhověkost